Spectroscopy, Microscopy and Fluorescence Imaging of Origanum vulgare L. Basis for Nondestructive Quality Assessment1. (9th August 2013) - Novo, Johanna M.; Iriel, Analia; Claudia Marchi, María; Gabriela Lagorio, María
Abstract: The organs of Origanum vulgare L. plant were examined by optical microscopy, scanning electron microscopy and autofluorescence imaging. The different organs were also studied spectroscopically. Fluorescence emission spectra were recorded for intact inflorescences, leaves and stems. Several fluorescence ratios (Blue/Red, Blue/Far‐red, Green/Red and Green/Far‐red), which varied depending on the considered organ of the plant, were derived. For leaves, a dependence of fluorescence spectra with water content was obtained as well. The intact samples were also analyzed by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy. These spectra were transformed to the Remission function depending on the wavenumber and two absorption bands (811 and 1740 cm −1 ), which displayed differences according to the plant organ sampled, were detected. These results were consistent with higher carvacrol content in inflorescences. The spectroscopic results were connected with the microscopic observation and with the presence of relevant nutraceutics contained in the plant. The optical indexes derived in this work may serve as potential indicators to be explored in the development of nondestructive methods for oregano quality assessment. Abstract : Origanum vulgare L. plant was studied spectroscopically and microscopically. The main achievement of this work was obtaining optical indicators related to nutraceutics and water content. A comprehensive description of the places where these optical signals are originated is presented.